ELECTROCHEMICAL ANALYSIS ON OUTPUT CURRENTS OF NEUTRINO ANTINEUTRINO-SENSITIVE APPARATUS - Nur Aida; Kenji Ishibashi; Shouhei Nakamura; Soya Tsuda; Ima Hayashi (AGRIBUSINESS JOURNAL, 2018)
We analyze the interaction of antineutrinos with water particle in electrochemical detectors. We postulate that some biological products generate a scalar auxiliary field B0 which breaks low-energy antineutrinos into boson vb and fermion v f particles. Low-energy anti neutrinos are suggested to interact with water molecules and produce output currents. We examine the output current of neutrino interactions in the electrochemical apparatus with chemical-reaction equations and half-cell model under postulated influence of weak interaction. The environmental neutrino is analysed. The output currents are treated to be generated by hydrogen ion and oxygen with the half-cell model with inclusion of weak interaction effect on hydrooxide ion recombination.